Anglicyzmy w konfrontatywnym nauczaniu języka rosyjskiego - Woch, Joanna (Neofilolog, 2024)
Russian language acquisition by Polish students is understood as effective and appropriate interaction in various conversational situations. This requires specific habits in the use of the contemporary Russian linguistic system. The use of a language can be examined in a natural communicative situation, which needs informal, spoken language. The usage of English loanwords in spoken Polish and Russian is frequent, which is why the characteristics of spoken language in contemporary spoken Russian and Polish needs to be examined. Research conducted on a group of Polish, Russian, Belorussian and Ukrainian Youtubers shows that their speech contains some specific derivatives which are characteristic of colloquial Russian and Polish. It also contains groups of English loanwords: assimilated nouns, verb and adjective derivatives with productive suffixes. The study shows that English loanword adaptation differs in Polish and Russian, which reveals system differences between two related languages. Comparison of the most productive word formation processes in Russian and Polish can help to overcome language interference and improve the teaching of Russian to Polish students in general.